Urban and rural coarse aerosol mass across the United States: Spatial and seasonal variability and long-term trends. (1st December 2019) - Hand, J.L.; Gill, T.E.; Schichtel, B.A.
Abstract: Coarse aerosol mass (CM = PM10  − PM2.5, mass of particles with aerodynamic diameters between 2.5 and 10 μm) has important environmental and climate impacts. Examining the spatial and temporal variability of CM is important for understanding its sources and transport, evaluating its environmental impacts, and designing mitigation strategies. CM was computed at 195 collocated U.S. Environmental Protection Agency (EPA) PM10 and PM2.5 Federal Reference Method (FRM) sites from 2000 through 2016. These data were integrated with remote/rural CM data at 155 sites from the IMPROVE (Interagency Monitoring of Protected Visual Environments) network to create a continental-scale dataset of daily, monthly, seasonal, and annual mean CM concentrations, as well as regionally aggregated data. Annual mean average continental United States (CONUS) urban CM concentrations were twice that of rural CM concentrations (10.5 μg m −3 versus 4.9 μg m −3, respectively) for 2012–2016. The highest CM concentrations occurred in the Southwest in spring, the central United States in summer and fall, and southern California nearly year-round. The lowest CM concentrations occurred in the Intermountain West, northwestern United States, and regions in the East. While urban CM concentrations were higher, CONUS average urban and rural CM/PM10 fractions were similar, with an annual mean fraction of 0.5. However, many regions, especially across the West, experienced much higher fractions (>0.7) depending on season. Regional mean CM weekly cycles with lower weekend concentrations were observed at both urban and rural sites throughout most of the country, indicating anthropogenic influence. Trend analyses suggest spring and summer mean CM has increased significantly at some remote and urban sites over the 2000–2016 period, especially at sites in the central and eastern United States. However, CONUS annual mean urban CM has decreased significantly (p < 0.05) at a rate of −1.8% yr −1 compared to an insignificant increase of 0.5% yr −1 at rural sites. Urban and rural relative contributions of CM to PM10 have increased since 2000 due to the strong reductions of PM2.5 mass. Understanding CM seasonal and temporal variability, composition, and sources is increasingly important in order to develop effective mitigation strategies for managing its environmental and climate impacts. Graphical abstract: Image 1 Highlights: Coarse aerosol mass was computed for urban and rural sites across the U.S. Urban coarse mass concentrations were two times higher than rural coarse mass. Urban coarse mass has decreased at a greater rate than rural coarse mass.